1989
DOI: 10.1152/ajpendo.1989.256.2.e331
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide receptor antagonist human CGRP-(8-37)

Abstract: From this study, we predicted that the human calcitonin gene-related peptide (hCGRP) fragment hCGRP-(8-37) would be a selective antagonist for CGRP receptors but an agonist for calcitonin (CT) receptors. In rat liver plasma membrane, where CGRP receptors predominate and CT appears to act through these receptors, hCGRP-(8-37) dose dependently displaced 125I-[Tyr0]rat CGRP binding. However, hCGRP-(8-37) had no effect on adenylate cyclase activity in liver plasma membrane. Furthermore, hCGRP-(8-37) inhibited aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
178
0
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(188 citation statements)
references
References 15 publications
6
178
0
2
Order By: Relevance
“…Further in vivo experiments are needed to define the effects of inhibition of CGRP release from sensory nerves on insulin-mediated glucose metabolism, utilizing specific CGRP receptor antagonists [35] and capsaicin receptor antagonists [5]. The use of such antagonists and neonatal capsaicin treatment will help to define more clearly the role of CGRP and other neuropeptides in animal models of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Further in vivo experiments are needed to define the effects of inhibition of CGRP release from sensory nerves on insulin-mediated glucose metabolism, utilizing specific CGRP receptor antagonists [35] and capsaicin receptor antagonists [5]. The use of such antagonists and neonatal capsaicin treatment will help to define more clearly the role of CGRP and other neuropeptides in animal models of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently suggested that CGRP-R antagonists could be effective in treating migraine (19). To address this issue, we used three selective CGRP-R antagonists: MK-8825, a new and selective CGRP antagonist with a good oral bioavailability in rodents (25); BIBN4096BS (olcegepant), a high-affinity antagonist with established clinical efficacy in migraine (26-28); and CGRP 8-37, the first peptidic CGRP fragment used as a CGRP-R antagonist (29,30). We first induced a CSD episode in the control condition by bath application of 26 mM KCl.…”
Section: High Potassium Concentration Evokes Reproducible Csd In Rat mentioning
confidence: 99%
“…CGRP plays a crucial role in producing vasodilation and maintaining low vascular resistance by binding to the CGRP-1 receptor (Jansen-Olesen et al, 2001;Brain and Grant, 2004,). CGRP 8−37 , a classic antagonist of CGRP-1 receptor, has been used to block CGRP-induced vasodilation (Chiba et al, 1989). Intravenous or paw injection of CGRP 8−37 attenuates SCS-induced vasodilation at all intensities (Tanaka et al, 2001;.…”
Section: Antidromic Mechanism-mentioning
confidence: 99%